Deficiency of Vitamin D in Patients with Chronic Liver Disease - Ali, Kashif; Iqbal, Mujahid; Zahra, Nalain; Abbas, Nadir; Buzdar, Irfan; Zafar, Shehriyar (Biological and Clinical Sciences Research Journal, 2025)
Deficiency of Vitamin D is associated with various types of chronic liver diseases and with a higher risk of death in these patients. Therefore, it is crucial to diagnose and treat Vitamin D deficiency in patients with chronic liver disease. Objective: The objective of this study was to find out the frequency of vitamin D deficiency in patients with chronic liver Disease. Methods: The present cross-sectional study was conducted at the Department of Medicine, Allama Iqbal Teaching Hospital, DG. Khan from January 2025 to June 2025. After obtaining permission from the institute’s ethics board, a total of 167 individuals, including both genders and aged 18 to 50, who had been diagnosed with chronic liver disease for more than six months and received at least 15 minutes of sun exposure twice a week, were included in this study. Data was collected from patients in the hospital’s Medicine and Gastroenterology department who satisfied the inclusion criteria. The data were analyzed using SPSS version 20. Percentages and frequencies were calculated for vitamin D deficiency, gender, and the causes of chronic liver disease (HBV/HCV/alcohol/Wilson’s disease, etc.). We determined the mean and standard deviations for socioeconomic status (monthly income), age, BMI, SGPT, vitamin D levels, and sun exposure. To determine the connection between variables, the chi-square test was used. A p-value of less than 0.05 was considered to be statistically significant. Results: A total of 167 individuals with chronic liver disease were enrolled in this study, out of which 106(63.4%) were male and 61(36.5%) were female. A deficiency of vitamin D was observed in 95 (56.88%) individuals. The most common cause of chronic liver disease was HCV 140(83.8%). Our study found that vitamin D insufficiency was significantly associated with the cause of CLD, but not with age, gender, BMI, socioeconomic level, or sun exposure. Conclusion: Our study found that vitamin D insufficiency was prevalent in patients with CLD (56.8%), with a higher incidence in men.